Evaluation of Antifungal Analysis of Selected Food Products Obtained In the Local Markets of Peshawar KPK Pakistan - Ullah, Shakir; Khan, Hayat; Zubair, Yasir; Zubair, Muneeba; Saeed, Usman; Bibi, Maryam; Ahad, Eidul; Ullah, Zeeshan; Gohar, Adam khan; Shah, Usman; Rahman, Sadiq Ur; Rahman, Muhammad Iqbal Khan (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Foodborne diseases are very easily transmitted from contaminated food and food handlers. Bacteria and fungi are the major factors for fruit spoilage. Food spoilage causes losses to producers, distributors, and consumers in the form of reduced quality and quantity and higher prices. The objective of this study was to isolate and evaluate the antifungal analysis of food-borne fungal pathogens. For the evaluation of pathogenic fungi Milk, Chutney, Apple, Spinach, Salad, Guava, Fish, and Peas were taken. All the other food samples were taken in polythene zip bags. The vegetables and fruits were cut into small pieces with a sterilized blade and then plated on Sabouraud dextrose agar (SDA) aseptically and then incubated for 5 days. To find foodborne pathogenic fungi in various food items, a total of 320 were collected for evaluation. Out of the total food samples (65), 20.31% were found positive for fungal pathogens in various foodstuffs while 255 (79.68%) food samples were found negative. Among the positive food samples, Fusarium spp was more predominant 28(43%) led by Aspergillus spp 25( 38.5%). In comparison, Mucor and Cladosporium were found in low frequency with percentages of 7(10.8%), 5(7.7%). For antifungal activity, a panel of selected drugs was used to assess the susceptibility of pathogens. Among the antifungals best activity was shown by Voriconazole and intermediate activity was shown by Fluconazole. While high resistance was observed in Nystatin as compared to other antifungals.